The occurence of complication in post punctured vasectomy vs standard method - Ishandono Dachlan Ishandono Dachlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Punctured Technique of Vasectomy is a simple and refined method of vasectomy. This method was introduced to make fewer complications and to remove the fear of surgical knife.Objective: This study was aimed to assess the ease of procedure, safety, and effectiveness of Punctured Technique of Vasectomy.Methods: A prospective study of 80 acceptors has been done at Dr. Sardjito Hospital Yogyakarta from January 1991 up to Jury 1991. These subjects were randomly distributed into two groups, Punctured Method (39) and Standard Method (41). Duration of operation and complication done during operation was recorded. The follow up for complication was recorded in the second week post-operative, and sperm analyses was done in the tenth week post-operative.Results: Duration of Punctured Method (9,7179 Â± 2,9731 minutes) was significantly different (p-value =0,0006) compared to that of Standard Method (12,1951 Â± 3,2421 minutes). There were two complications during Punctured Method operation compared to six complications during Standard Method operation (RR =1,54; 95%Cl: 0,97 - 2,46). In the second post-operative week, there was no complication in the Punctured Method group, while there was one wound infection in the Standard Method group. Sperm analysis both groups showed no active spermatozoon.Conclusion: Punctured Method is easier than Standard Method, and there was no difference of effectiveness in both methods.Key words: punctured vasectomy - complications - sperm - analysis